Estimating minimal clinically important differences of upper extremity measures early after stroke - Lang, Catherine E. (2008)
OBJECTIVE: To estimate minimal clinically important difference values of several upper extremity measures early after stroke. DESIGN: Data in this report were collected during the VECTORS trial, an acute, single-blind randomized controlled trial of Constraint Induced Movement Therapy. Subjects were tested at the pre-randomization baseline assessment (average of 9.5 days post stroke), and the first post-treatment assessment (25.9 days post stroke). At each time point, the affected upper extremity was evaluated with a battery of 6 tests. At the second assessment, subjects were also asked to provide a global rating of perceived changes in their affected upper extremity. Anchor-based minimal clinically important difference values were calculated separately for the affected dominant upper extremities and the affected non-dominant upper extremities for each of the 6 tests. SETTING: Inpatient rehabilitation hospital. PARTICIPANTS: Fifty-two people with hemiparesis post stroke. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: Estimated minimal clinically important difference values for grip strength, composite upper extremity strength, Action Research Arm Test (ARAT), Wolf Motor Function Test (WMFT), Motor Activity Log (MAL), and duration of upper extremity use as measured with accelerometry. RESULTS: Minimal clinically important difference values for grip strength were 5.0 and 6.2 kg for the affected dominant and non-dominant sides respectively. Minimal clinically important difference values for the ARAT were 12 and 17 points, for the WMFT Function score were 1.0 and 1.2 points, and for the MAL How well score were 1.0 and 1.1 points for the two sides respectively. Minimal clinically important difference values were indeterminate for the dominant (composite strength), the non-dominant (WMFT Time score) or for both affected sides (duration of use) for the other measures. CONCLUSIONS: Our data provide some of the first estimates of minimal clinically important difference values for upper extremity standardized measures early after stroke. Future studies with larger sample sizes are needed to refine these estimates and to determine if minimal clinically important difference values are modified by time post stroke.